Efektivitas Sosialisasi Berbasis Komunitas dalam Mencegah Stunting pada Ibu Hamil Dan Remaja Putri di Desa Bakalan - Azizah, Nur; Susilo, Taufik Eko; Rahman, Farid; Naufal, Adnan Faris; Pristianto, Arif; Fatmarizka, Tiara (Pakis Journal Institute, 2025)
Stunting is a nutritional issue that remains a concern in various regions. This problem can affect children's growth and development and has long-term impacts on health conditions. In Bakalan Village, many community members still lack sufficient understanding of stunting. This program aims to raise awareness among pregnant women and adolescent girls about the importance of nutrition in early childhood growth and development. The method applied to enhance understanding among pregnant women and adolescent girls involves direct educational counseling through socialization and assessing their comprehension using pre-tests and post-tests. The results indicate that the implemented educational program effectively increased public awareness and understanding of stunting prevention, with the participants' average pre-test score being 6.50, rising to 7.80 in the post-test with statistical significance (p=0.000).